JUDICIAL REVIEW PUTUSAN MAHKAMAH KONSTITUSI TERHADAP UNDANG-UNDANG PENODAAN AGAMA - Fatimah Azzahra; Naela Rosita; Amiratunil Khaira (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The judicial review of Law No. 1/PNPS/1965 on the Prevention of Religious Abuse and/or Blasphemy has sparked significant legal and constitutional discourse in Indonesia. This law, which was enacted during the Guided Democracy era, has often been criticized for conflicting with post-amendment constitutional norms, particularly those related to human rights and religious freedom. The purpose of this study is to examine, from a multidisciplinary legal perspective, the Constitutional Court's interpretation and reasoning in three major decisions: Case No. 140/PUU-VII/2009, No. 84/PUU-X/2012, and No. 56/PUU-XV/2017. Using a normative juridical approach and descriptive qualitative method through library research, this paper analyzes the arguments presented by the petitioners, the government, and the Court, including dissenting and concurring opinions. The findings of this study indicate that the Court consistently upheld the constitutionality of the blasphemy law, arguing for the importance of public order and religious harmony. However, the rulings also reveal an ongoing tension between majority religious interests and the protection of minority rights. This study concludes that while the law remains valid, its application risks undermining legal certainty, equality before the law, and freedom of religious expression in a pluralistic society.